1954
DOI: 10.1113/jphysiol.1954.sp005039
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the mechanism of circulatory autoregulation in the perfused dog's kidney

Abstract: The blood flow through the dog's kidney tends to remain constant despite changes in perfusion pressure. The early observations on this subject have been reviewed by Winton (1937), and recently Selkurt (1951) and Shipley & Study (1951) have shown that the range of perfusion pressure over which the renal flow remains relatively unchanged lies between approximately 90-190 mm Hg. This phenomenon may be present in the isolated kidney and has been referred to as circulatory 'autoregulation'; as it is not known wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1958
1958
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 5 publications
(3 reference statements)
1
11
0
Order By: Relevance
“…In these latter studies, RBF autoregulation of the perfused dog kidney remained intact despite perfusate P o 2 as low as 3-7mmHg. It should be noted, however, that interruption of renal oxidative metabolism and induction of histotoxic hypoxia by large doses of intrarenal cyanide may interfere with RBF autoregulation [16]. Together the results of the present studies in vivo and previous perfused kidney studies suggest that RBF and GFR autoregulation occurs despite moderate to profound decreases in arterial or perfusate Po2.…”
Section: Discussionmentioning
confidence: 65%
“…In these latter studies, RBF autoregulation of the perfused dog kidney remained intact despite perfusate P o 2 as low as 3-7mmHg. It should be noted, however, that interruption of renal oxidative metabolism and induction of histotoxic hypoxia by large doses of intrarenal cyanide may interfere with RBF autoregulation [16]. Together the results of the present studies in vivo and previous perfused kidney studies suggest that RBF and GFR autoregulation occurs despite moderate to profound decreases in arterial or perfusate Po2.…”
Section: Discussionmentioning
confidence: 65%
“…Thus, as is the case for the kidney perfused with Ringer's solution, r> -° the change in renal resistance when arterial pressure is varied may be concerned largely with the factors determining an abnormally high intraronal pressure. Tn kidneys poisoned with cyanide, the interstitial pressure rises markedly 1 and rectilinear blood pressure-flow data are found.-• 3 A similar relationship between renal arterial pressure and flow has also been observed for an oxygenated colloidal perfusate devoid of red blood cells. * A water-immiscible Newtonian liquid would seem to be an ideal perfusate to determine the purely physical effects of arterial pressure on the dimensional vascular component of renal resistance.…”
mentioning
confidence: 66%
“…To assure removal of blood, the heparinized excised kidneys were perfused fii-st with 500 ml. of 1.5 per cent sodium chloride solution 1 " at an arteri'il pressure of 100 mm. Hg.…”
Section: Meteiods and Materialsmentioning
confidence: 99%
“…A utoregulation o f blood flow through the ren al vascular bed is probably b e t t e r documented (25,29,30,32,34,40,42,48,56,58) than in any other organ in the body. I t has been demonstrated in in ta c t kidneys (29), is o la te d kidneys (25), kidney perfused with oxygenated dextran (25), and in decapsulated kidneys (25).…”
Section: A Utoregulationmentioning
confidence: 99%
“…However, Haddy e_t a l. (26) found that renal au to reg u latio n was not associated with a s ig n ific a n t change in the rate o f lymph flow from the kidney. Also, autoregulation is said to be abolished upon in a c tiv a tio n of vascular smooth muscle (25,40,42).…”
Section: Introductionmentioning
confidence: 99%